Antigenic structure of transmissible gastroenteritis virus nucleoprotein - Martín Alonso, J.M. (Virology, 1992)
A group of 11 monoclonal antibodies (MAbs) raised against transmissible gastroenteritis virus (TGEV) was used to study the antigenic structure of the virus nucleoprotein (N). To identify the regions recognized by MAbs, DNA fragments derived from the N-coding region of the TGEV strain FS772/70 were cloned into pUR expression plasmids and the antigenicity of the resulting fusion proteins was analyzed by immunobloting. A major antigenic domain was identified, covering the first 241 amino acid residues of N, within which an epitope (residues 57–117) was also found. A second antigenic domain extended from residues 175 to 360 of the nucleoprotein, within which a subsite was characterized within the region covering residues 241–349. MAb DA3 recognized a linear epitope which mapped within residues 360 and 382 at the carboxy terminus of the nucleoprotein. The binding of the majority of the MAbs (8 out of 11) to large fusions, but not to smaller fragments included in them, suggests a conformational dependence of the MAb binding sites. Our data show that the use of fusions in Western blot experiments is a useful approach to map not only linear epitopes but more complex antigenic structures found in the nucleoprotein of TGEV.